Terpene volatiles mediates the chemical basis of blueberry aroma and consumer acceptability. (August 2022) - Ferrão, Luís Felipe V.; Sater, Haley; Lyrene, Paul; Amadeu, Rodrigo R.; Sims, Charles A.; Tieman, Denise M.; Munoz, Patricio R.
Graphical abstract: Highlights: Volatile organic compounds (VOCs) emitted from blueberries produced the sensation of aroma, creating the myriad of flavors experienced. Aromatic notes were perceived differently by blueberry consumers and had a positive flavor sensation. At the chemical level, a group of eight terpene volatiles constituted the primary metabolic group associated with aroma sensation in blueberry. Aromatic genotypes can be classified using metabolomics data. When combined with pedigree analyses, metabolomic information can be used for flavor-assisted selection in fruits. Abstract: Flavor is among the most important traits valued by consumers of fresh fruits. Human perception of flavor occurs primarily through two main sensory inputs, taste and aroma. Through retronasal olfaction, volatile organic compounds (VOCs) emitted by the fruit are able to produce the sensation of aroma which when combined with gustatory inputs from the tongue together underly our perception of the thousands of flavors we experience throughout our lives. In blueberry, breeders have observed that some genotypes possess berries with unique 'floral' and 'sweet' flavor and aroma notes. The potential impact these characteristics might have on consumer acceptability is largely unknown and represents an opportunity to better understand how aroma attributes affect the perception of blueberry flavor. In this study, we dissected the main components of blueberry aroma and associated it with consumer predilections by pairing metabolomics with sensory analysis. Our contribution in this study is four-fold: (i) first, we differentiated genotypes with floral and sweet aroma notes and confirmed that such characteristics are preferred by consumers; (ii) at the chemical level, we showed that a group of eight terpenoid volatiles ( p -cymene, myrtenal, linalool, L-carvenol, geranyl acetone, geranyl acetate, D-limonene and β-myrcene) constitute the primary metabolic group associated with these aroma sensations; (iii) we demonstrated that aromatic genotypes can be classified using metabolomics; and finally, (iv) we combined pedigree and metabolomic information and showed the importance of metabolomic data for flavor-assisted selection. Our findings open new avenues to explore the phenomenon of flavor in blueberries and also allow us to present an emerging view about flavor and provide a detailed blueprint of how this targeted trait could be addressed in fruit and vegetable breeding.